Bahasa Indonesia Bahasa Indonesia - Sebayang, Melya Dyanasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Disturbances in the eyes of the elderly will cause disturbance which have an impact on discomfort and other disturbances in carrying out daily activities. The figure of the elderly is part of family members and community members whose number is increasing in line with the increase in life expectancy. The number of elderly people in Indonesia is increasing rapidly every year, so that Indonesia is expected to experience an “elderly population boom” in the early 2 decades of the 21 century as a result of the baby boom several decades ago. BPS projects that ini 2045 Indonesia will have around 63,31 million elderly or nearly 20 percent of the population. According to UN projections, the percentage of elderly Indonesians will reach 25 percent in 2050 or around 74 million elderly. This community service activity is a form of application in the optics and wave physics course. The purpose of this screening is to find out the description of eye refraction abnormalities and lectures can apply it to the community. The location for the screening was held in the Sei Agul area of Medan, North Sumatera. The subjects were the ederly and the poor around Medan Barat District who ere suspected of having refractive errors. Screening was carried out using the Snellen Optotype and corrected using a trial lens. The implementation of this community service activity took place smoothly and efficiently. The results of the exmation of the elderly, which were almost large, were that the elderly were not found to have eye defects such as night blindness, cataracts or color blindness. This activity is expected to foster community motivation in carrying out their lives with the glasses provided by the lion clubs and remind them to carry out routine checks before experiencing cataracts.